Butane-induced acute global myocardial ischemia without coronary artery pathology - Grigorov, Vladimir (Oxf Med Case Reports, 2020)
The case report describes a case of acute myocardial ischemia precipitated by propane butane inhalation. The dependency of this substance around the world is still moderate but is increasing due to the easy availability of the substance and the facility with which the effects can be concealed. The toxicity of the substance is significant; affecting the heart, the brain and the liver. The most common outcome is sudden death. In this article, we describe a survivor after an episode of acute poisoning and his interesting cardiac pathology.